Cluster-based spectrum sensing scheme in heterogeneous network - Hasan M.K.; Ismail A.F.; Abdalla A.-H.; Ramli H.A.M.; Islam S.; Hashim W.; Badron K. (Springer Verlag, 2023)
Energy dispersive spectroscopy; Intelligent systems; Monte Carlo methods; Orthogonal frequency division multiplexing; Signal detection; Cluster formations; Co-operative spectrum sensing; Heterogeneous Network (HetNet); Intercell interference; Multiple-channel detections; Spectrum allocation; Spectrum detection; Spectrum sensing; Heterogeneous networks